Identification of Secondary Metabolites in Flammulina velutipes by UPLC-Q-Exactive-Orbitrap MS - Ying Ding; Sitan Chen; Honglin Wang; Shanlei Li; Changyang Ma; Jinmei Wang; Lili Cui (Journal of Food Quality)
Flammulina velutipes is the fourth largest edible fungus in China with high nutritional value. In this paper, ultrahigh-performance liquid chromatography tandem hybrid quadrupole-Orbitrap mass spectrometry (UPLC-Q-Exactive-Orbitrap MS) was used to identify the secondary metabolites of F. velutipes. The metabolites were identified by comparing the retention time, accurate molecular weight, and MS2 data with standard databases of mzVault and mzCloud (compound: 17,000+) and BGI high-resolution accurate mass plant metabolome database (plant metabolite: 2500+). Finally, 26 secondary metabolites were preliminarily identified, including flavonoids, phenylpropanoids, organic acids, and steroids.